Nucleon - Goodman, Jim (JOURNAL OF ADVANCES IN PHYSICS, 2017)
The force here is the nuclear force binding the nuclei together. A magnetic dipole has the energy given by -13.6*2*n^2[3]. A particle with n=822 is a magnetic dipole with magnetic quantum number m=1,2,3,… so that -18.3786Mev*m is an energy/mass which we may associate with the nucleus. The relativistic correction 2[4] is required showing that the dipole velocity is near c. The nuclei are bound with particles of mass 18Mev consisting of 6 magnetic dipoles each. The binding energy tracks very well with Z-1 particles where Z is the atomic number of the element. The particle is named a Nucleon after the manner of graviton and should not be confused with the common name for a nuclear particle (proton or neutron).